Profile of Antibiotic Use in ENT Polyclinic at Siti Rahmah Islamic Hospital Padang in 2018 - Seres Triola (Science Midwifery, 2022)
The purpose of this study was to analyze the profile of antibiotic use in the ENT polyclinic at Siti Rahmah Islamic Hospital Padang in 2018. This study used a qualitative type of research with categotic descriptive analysis and a cross sectional research design. This approach was used to find out the magnitude of the problem from the Profile of Antibiotic Use in the ENT Poly at the Siti Rahmah Islamic Hospital Padang in 2018. The population that was the target of the study were patients using antibiotics in the ENT poly. Based on the description of the profile of antibiotic use in the ENT polyclinic at the Siti Rahmah Padang Islamic Hospital in 2018, it can be concluded that: 1) The majority of antibiotic users are women; 2) The majority of antibiotic users are 26-45 years old; 3) The majority of diagnoses were tonsillitis; 4) The majority of antibiotics are cefixime; and the majority of drug dosage forms are tablets.